Assessing local health outcomes using spatially-resolved health surveillance data - Henry, N (2022)
Complete and accurate health information systems are necessary inputs for effective health policy. Although many countries maintain civil registration and infectious disease surveillance systems, variation in data completeness often impedes analysis of aggregated health records at the spatial level where policymaking occurs, discouraging greater investment in these systems.